Bending vibrations of a thin wing for a profile with two axes of symmetry - Thao, Hoang Thi Minh; Thanh, Le Thi (Zielona Góra: Uniwersytet Zielonogórski)
In this work, we study the bending vibrations of a thin wing for a profile with two axes of symmetry, taking into account the influence of torsional vibrations on them. The primary focus of the current study is on finding an analytic solution for the wing-bending equation through the Laplace transform, determining the frequency of free-bending vibrations, and constructing the amplitude-frequency response and phase-frequency response of the wing.
Keywords: torsional vibrations; bending vibrations; airfoil with two axes of symmetry; Mach number; natural frequencies